Wirkungen serieller H2S-Mineralwasserbäder auf Schmerzen bei Patienten mit Fibromyalgiesyndrom – eine Pilotstudie - Nugraha, B.; Neues-Lahusen, M.; Candir, F.; Gutenbrunner, C. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2011)
Since the difficulties to provide effective treatment for fibromyalgia syndrome (FMS) patients, several studies have been performed in order to find best treatment, including pharmacological and non-pharmacological treatments. One of possibilities in non-pharmacological treatments for chronic pain patients is balneotherapy. Sulphur bath treatment is one of balneotherapies which is known as being useful for pain patients. Our previous studies showed that sulphur bath treatment could reduce the pain in rheumatoid arthritis patients. Hence, we evaluated the long term effect of sulphur bathing in FMS patients.In this study, we investigated 32 female FMS patients who matched the criteria of American College of Rheumatology. The patients were randomized into 2 groups. First group was treated with sulphur based bath (20.4 mg/l) and the control group which was only treated with tap water. Both groups were treated 3 times a week for 4 weeks. Main outcome parameter was Lautenschläger pain score. Additional parameters were pressure and heat and cold pain thresholds.Lautenschläger pain score significantly reduced in 4 week duration serial sulphur bath but not in control group (treatment group: x= − 16.6±3.6; control group: x=3.8±4.1; p<0.001). However, the effect did not show statistically significance after 3 months of follow-up. In addition, after 4 weeks of treatment, pressure pain threshold values were significantly different in sulphur bath group compared to control group (treatment group: x=10.6±0.2; control group: x=3.7±1.9; p<0.05). This effect was not seen in heat pain (treatment group: x= − 0.19±0.1; control group: x=2.5±1.4; p>0.05) and cold pain (treatment group: x= − 1.89±0.8; control group: x=− 2.0±0.6; p>0.05) thresholds.Although this study is only pilot study and only have small number of patients, however this study is promising that H2S could be an alternative methods for FMS treatment.
Keywords: fibromyalgia; musculoskeletal pain; rehabilitation medicine; sulphur bath